Citizen Science and Environmental Protection Agencies: Engaging Citizens to Address Key Environmental Challenges - Rubio-Iglesias, José Miguel; Edovald, Triin; Grew, Robert; Kark, Timo; Kideys, Ahmet Erkan; Peltola, Taru; Volten, Hester (Frontiers in Climate, 2020)
Environmental Protection Agencies (EPAs) have been involved in citizen science initiatives for decades, engaging with citizens with the goal of protecting and restoring our environment. Yet the data and knowledge generated, and the possibilities for engaging citizens have grown significantly in the last decades thanks to the recent developments in mobile technologies and the access to internet, resulting in a transformation of how environmental protection can be done. This Perspective provides some examples on how European EPAs and their partners are currently addressing key environmental challenges and exploring new institutional approaches by bringing in citizen science data and methods. It also points out challenges that need to be addressed to fully realize the potential of citizen science as a complement to the monitoring efforts by these agencies. Finally, it presents the Interest Group on Citizen Science of the Network of the Heads of Environmental Protection Agencies (EPA Network), an informal forum where EPAs across Europe share examples and bring together strategic insights on citizen science approaches into their daily activities.